An investigation into contextual facilitation effects from a verbal-visual format : a thesis presented in partial fulfilment of the requirements of the degree of Master of Education, Education Department, Massey University, Palmerston North, New Zealand - Hyde, Justin Charles Francis (Massey University, 1992)
This study investigated the use of contextual facilitation in children's beginning reading. A verbal-visual format was utilised to examine the way context influences children's ability to identify irregular words (words which do not follow normal spelling to sound relationships). The study also determined whether poor or good readers in each grade utilised context more or less according to a proposed stage pattern of word identification. The sample, comprised 113, children drawn from three grades from a Primary School in New Plymouth. Children were individually tested with the Peabody Picture Vocabulary Test-Revised, BURT Word Reading Test, Isolated Word Test and Contextual Facilitation Test. The BURT, Isolated Word Test and Context Facilitation Test were modified for easier presentation and active participation of the children to reduce confounding variables of earlier research. Two ANOVA's were applied to analyse data in this study. The first was used to assess the difference that exists in contextual facilitation across the grades tested. The second ANOVA assessed the interaction between grade by reading ability by word block difficulty for context facilitation and for movement through the proposed stage pattern in word recognition. A correlation and stepwise regression assessed the link between context facilitation and BURT scores for reading ability differences between the children in relation to contextual facilitation use. The first ANOVA revealed that utilisation of context with childrens' increasing age decreases for simple words, but increases with increasing word difficulty. The second ANOVA indicated a divergence in reading ability and contextual facilitation beginning at about Junior 2 grade, which possibly delayed childrens' development of automatic word decoding skills. The correlation and stepwise regression between contextual facilitation and BURT scores provides the range of the children's word identification ability. This showed a considerable range in ability from poor word decoding where context cannot be utilised, through an alliance between decoding and context to identify words; to highly efficient word decoding without the need for context. Evidence from this study indicates the existence of a stage pattern of sight word acquisition similar to that proposed by Adams and Huggins (1985). This consists of three stages: 1) non-recognition, 2) intermediate and 3) automatic word recognition. Results of. this study provide evidence that an alliance exists between children's decoding and context for words in the intermediate stage before automatic word recognition occurs. As a result, increasing word identification ability into the child's non-recognition stage from intermediate stage expansion. Divergence in the stage pattern proposed begins in Junior 2 grade, where low ability readers lag behind in automatic word decoding and rely more on context. Further research beyond the generalised results from this study should include a longitudinal study to follow the reading development of individual students.
Keywords: Literacy; Evaluation; Literacy programs; Reading comprehension; Study and teaching; Reading